Medicine expenses and obesity in Brazil: an analysis based on the household budget survey. (December 2015) - Canella, Daniela; Novaes, Hillegonda; Levy, Renata
Abstract Background Obesity can be considered a global public health problem that affects virtually all countries worldwide and results in greater use of healthcare services and higher healthcare costs. We aimed to describe average monthly household medicine expenses according to source of funding, public or private, and to estimate the influence of the presence of obese residents in households on total medicine expenses. Methods This study was based on data from the 2008–2009 Brazilian Household Budget Survey, with a representative population sample of 55, 970 households as study units. Information on nutritional status and medicines acquired and their cost in the past 30 days were analyzed. A two-part model was employed to assess the influence of obesity on medicine expenses, with monthly household medicine expenses per capita as outcome, presence of obese in the household as explanatory variable, and adjustment for confounding variables. Results Out-of-pocket expenses on medicines were always higher than the cost of medicines obtained through the public sector, and 32 % of households had at least one obese as resident. Monthly household expenses on medicines per capita in households with obese was US$ 20.40, 16 % higher than in households with no obese. An adjusted model confirmed that the presence of obese in the households increased medicine expenses. Conclusion Obesity is associated with additional medicine expenses, increasing the negative impact on household budgets and public expenditure.